Technology and Equipment for Underwater Robots - Yinglong Chen; Fei Gao; Cheng Zhou; Xinyu Yang; Xingtian Xiao; Bo Yan (Journal of Marine Science and Engineering)
As more and more attention is paid to marine resources and furthering marine scientific research, underwater robots, offering unique advantages and great potential, are playing an indispensable role in many respects, including in deep-sea exploration, marine ecological monitoring, salvage and rescue, and underwater engineering operations [...]